Peran Keterampilan Sosial Emosional (KSE) terhadap Kesiapan Psikologis Murid Kelas VI SD dalam Menghadapi Tes Kemampuan Akademik (TKA) - Nur Hidayati; Moch Widjanarko; Indah Lestari (Pusat Riset dan Inovasi Nasional, 2026)
The implementation of the Academic Ability Test (TKA) at the elementary school level requires not only students’ cognitive readiness but also psychological readiness to enable them to cope adaptively with evaluation-related pressure. One factor believed to play an important role in developing psychological readiness is Social Emotional Learning (SEL), which include self-awareness, self-management, social awareness, relationship skills, and responsible decision-making. This study aims to analyze the role of Social Emotional Skills in the psychological readiness of sixth-grade elementary school students in facing the Academic Ability Test. This research employed a quantitative approach with a correlational design. Data were collected through a Likert-scale questionnaire administered to sixth-grade students at SDN 1, 2, and 3 Ngetuk, Ngetuk village, Nalumsari district, Jepara regency. Data analysis was conducted using correlation analysis and simple linear regression. The results indicate a significant positive relationship between Social Emotional Learning and students’ psychological readiness. Regression analysis further reveals that Social Emotional Skills make a substantial contribution to students’ psychological readiness in facing the Academic Ability Test, indicating that higher levels of Social Emotional Learning are associated with higher levels of psychological readiness. These findings confirm that Social Emotional Skills play a crucial role in fostering mental resilience, self-confidence, and students’ ability to manage anxiety when confronting nationally standardized academic assessments. The implications of this study suggest that elementary schools in Indonesia need to systematically integrate the development of Social Emotional Learning into instructional practices and school culture to ensure that students possess optimal psychological readiness when undergoing nationally standardized academic evaluations such as the Academic Ability Test.